Solving an Integral Equation via Orthogonal Branciari Metric Spaces. (6th April 2022) - Mukheimer, Aiman; Gnanaprakasam, Arul Joseph; Haq, Absar Ul; Prakasam, Senthil Kumar; Mani, Gunaseelan; Baloch, Imran Abbas
Abstract : In this article, we present an orthogonal L -contraction mapping concepts and prove a fixed point theorem on orthogonal complete Branciari metric spaces. As an application, we apply our major results to solving integral equations.